Particles in German, English, and beyond - Gergel, Remus, 1974-; Reich, Ingo; Speyer, Augustin (Studies in language companion series ;, 2022)
"Germanic languages have been recognized as having not only intensifying or focus particles, but also so-called modal particles. The relevant items are specialized discourse markers joined by characteristic syntactic properties. After an introductory overview of the complex field, the contributions of the current volume capitalize on, but also work much further beyond the baseline of the established insights. They offer analyses of (a) new data types within and sometimes across several Germanic languages (e.g. varieties/stages of German, Dutch, or Norwegian), encompassing different classes of particles and a variety of syntactic-semantic as well as usage-based aspects; (b) the classical dichotomy between languages like German and English when it comes to the availability of modal particles both synchronically and diachronically; (c) crucial integrated insight from non-Germanic languages such as French, Hungarian, Italian, Mandarin, or Vietnamese. A number of mostly interface-based proposals of several languages as well as further generalizations are put on the table for both expert and novice readers in the field"--